DAMAGE TO POLICY CROPS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Melons are very susceptible to pests and diseases, and if necessary, measures are not taken against them, most of the melon crops may be lost, or the plant may not yield at all. On melons feed on several dozen sucking and rodent pests, the most dangerous of which are considered spiders, cockerels, melon beetles and melons fly.